Historical and philosophical analysis of free will as the genesis of understanding law - Savchenko, Viktor (Revista Publicum, 2023)
A scientific article examines the historical and philosophical analysis of free will as the genesis of understanding law. The article considers the views of prominent scientists on the legal nature of free will. The article proves that historically, the main purpose of law was to regulate social relations and free will. The evolution of views on free will in law through Antiquity, the Middle Ages, the Reformation and modern understanding has been studied. The ideas of Antisthenes, Aristotle, Socrates, Plato, Cicero, Flaccus, Origen, Aurelius Augustine, Boethius, Bernard of Clairvaux, Giordano Bruno, Giovanni Pico della Mirandola, Martin Luther, F. Suarez, M. de Molpino, T. Spinoza, I. Fichte, G. Hegel, I. Kant, F. Schelling, Cohen, L. Feuerbach, A. Schopenhauer, J. Locke, G. Leibniz, K. Marx, F. Nietzsche, E. Mounier, M. Heidegger, K. Jaspers, J. Sartre, R. Kane are explored.